Rivaroxaban vs. warfarin for the treatment and prevention of venous thromboembolism: A meta-analysis - Liu, Zhuang; Song, Dan; Wang, Liang; Wang, Changfeng; Zhou, Jie; Sun, Jiali; Guo, Lei (Frontiers in Surgery, 2023)
Background: The prevention and treatment of venous thromboembolism (VTE) is managed with anticoagulant therapy. However, the relative effectiveness of newer anticoagulants versus warfarin has not been assessed. Objective: To assess the effectiveness and safety of rivaroxaban versus warfarin for VTE through a meta-analysis of recent randomized controlled trials. Materials and methods: A comprehensive literature search of PubMed, EMBASE, Web of Science, and the Cochrane Library was conducted to retrieve all related studies from January 2000 until October 2021. Two reviewers screened the studies independently, extracted data, and appraised the quality of the included studies. The primary outcomes were VTE and bleeding events. Secondary outcomes were risks of each post-thrombotic syndrome category (mild, moderate, severe) and venous ulcer. Results: In total, 20 trials were retrieved. These studies involved 230,320 patients, of which 74,018 received rivaroxaban and 156,302 received warfarin. Compared with warfarin, rivaroxaban had a significantly lower incidence of VTE (risk ratio (RR) 0.71, 95% confidence interval (CI) [0.61, 0.84]; P < 0.0001, random effect model), and signiﬁcantly reduced major (RR 0.84, 95% CI [0.77, 0.91]; P < 0.0001, fixed effect model) and nonmajor (RR 0.55, 95% CI [0.41, 0.74]; P < 0.0001, fixed effect model) bleeding. There were no signiﬁcant differences in all-cause mortality (RR 0.68, 95% CI [0.45, 1.02]; P = 0.06, fixed effect model) between the two groups. Conclusion: This meta-analysis indicated that rivaroxaban signiﬁcantly reduced the incidence of VTE when compared to warfarin. However, well-designed studies with larger sample sizes are needed to corroborate these findings.